O01 Efficacy and safety of ALXN1840 versus standard of care in Wilson disease: primary results from an ongoing phase 3, randomized, controlled, rater-blinded trial. (20th September 2022) - Weiss, Karl Heinz; Schilsky, Michael; Czlonkowska, Anna; Askari, Frederick; Ala, Aftab; Ferenci, Peter; Ott, Peter; Abdurakhmanov, Dzhamal; Szalay, Ferenc; Socha, Piotr; Shimizu, Norikazu; Bronstein, Jeff; et al.
Abstract : Background and Aims: ALXN1840 is an oral, copper (Cu)-binding agent that forms a stable tripartite (tetrathiomolybdate-Cu-albumin) complex. This study investigated the efficacy and safety of ALXN1840 for treating Wilson disease (WD) using a novel plasma biomarker of Cu sequestration. Method: Patients with WD aged ≥ 12 years (Leipzig score ≥ 4; model for end-stage liver disease score ≤ 13) were randomized 2:1 to ALXN1840 at a starting dose of 15 mg QD with dose adjustments up to 60 mg QD permitted, or standard of care (SoC; penicillamine, trientine and/or zinc) for 48 weeks (W). Prior SoC for > 28 days and 0 – 28 days determined enrolment to Cohorts 1 and 2, respectively. Primary endpoint: mean daily area under the effect-time curve of directly measured non-ceruloplasmin-bound Cu 0 – 48W (dNCC AUEC0–48W). Secondary endpoints: 0 – 48W change in neurological Unified WD rating scale (UWDRS) Part II and III scores, and Clinical Global Impression – Improvement (CGI-I) scores. A pre-specified hierarchical statistical testing method was used to control multiplicity across primary and key secondary endpoints. Adverse events (AEs) were summarized. Results: 214 patients enrolled; all had preserved liver function and 79% had neurological symptoms. 207 were treated, 137 with ALXN1840 and 70 with SoC; mean age was 34.3 and 32.1 years, and 59.9% and 52.9% were male, respectively. Mean daily dNCC AUEC0–48W (μmol/L) was 3.2 times greater with ALXN1840 than with SoC overall (least-squares mean [LSM] difference, 2.18 [standard error (SE), 0.244], p < 0.0001), and 2.5 times greater with ALXN1840 for Cohort 1, despite a mean prior SoC duration of > 12 years ( figure 1 ). UWDRS scores reduced modestly from 0 to 48W (mean [95% confidence interval] change in Part III score for symptomatic patients: ALXN1840, –2.91 [–4.74, –1.09]; SoC, –1.17 [–3.20, 0.86]). No significant between-group differences occurred by 48W. Transformed CGI-I scores improved with ALXN1840 vs SoC at 48W; LSM difference, –0.3 [SE, 0.15], p = 0.0316; outside the multiplicity testing sequence). For 0 – 48W, 100.1 (ALXN1840) and 86.5 (SoC) patients experienced AEs per 100 patient-years. Most AEs (ALXN1840, 94.1%; SoC, 92.7%) were not serious. The most frequent AE with ALXN1840 was alanine aminotransferase increase (14.6%). Two deaths, considered unrelated to ALXN1840, were reported. Conclusion: ALXN1840 treatment for 48W provided superior Cu control to SoC and was generally well tolerated. Future data analysis of the 60-month open-label extension of this study will evaluate long-term efficacy and safety of ALXN1840.